AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL UMBI TAWAS UT (Ampelocissus rubiginosa Lauterb.) PADA MENCIT SECARA TOPIKAL - Deka Rotama; Noor Cahaya; Sudarsono Sudarsono; Agung Endro Nugroho; Khoerul Anwar (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Tawas ut tuber (Ampelocissus rubiginosa Lauterb.) contains of flavonoid, tanin, compound and saponin which is potentially anti-inflammatory. This objective of this research is to prove by effect giving extrak ethanol tawas ut tuber about effect anti-inflammatory topical based on consideration the fold of the skin and amount of cell neutrofil to mice which induced by carageenan. Thirty mice ware divided into 6 groups. They were normal control group (palacebo gel), positive control (Voltaren®), negative control (karagenin), and testing groups with gel extract concentrations of 0,5%, 1%, and 2%. Ethanol extract of Tawas ut tuber leaf applied, after back of test animals was induced by 0,2 ml of 3% carageenan, then every hour was measured for middosal skin fold thickness during 6 hours observation. The animal’s skin was cut off to perform test at 24 hours after treatment. The neutrophils migration was observed using hematoxylin and eosin (HE) stining method. The percentage result of inhibition (%PI) ethanol extrak of tawas ut tuber with concentration 0,5%, 1%, and 2% were 20,00%; 23,51%; and 24,92% respetively. The average result of netrofil total from ethanol extrak of tawas ut tuber with concentration 0,5%, 1% and 2% were 28,28; 20,88; and 16,24 respecively. Gel 2% posesses the most effective topical anti-inflammatory. Based on the result, it can be concluded that ethanol extrak of tawas ut tuber posesses anti-inflammatory in skin oedema of back of mice induced by carageenan.